Evolutionarily conserved amino acids in MHC-II mediate bat influenza A virus entry into human cells. - Okikiola M Olajide; Maria Kaukab Osman; Jonathan Robert; Susanne Kessler; Lina Kathrin Toews; Thiprampai Thamamongood; Jacques Neefjes; Antoni G Wrobel; Martin Schwemmle; Kevin Ciminski; Peter Reuther (PLoS Biology)
The viral hemagglutinins of conventional influenza A viruses (IAVs) bind to sialylated glycans on host cell surfaces for attachment and subsequent infection. In contrast, hemagglutinins of bat-derived IAVs target major histocompatibility complex class II (MHC-II) for cell entry. MHC-II proteins from various vertebrate species can facilitate infection with the bat IAV H18N11. Yet, it has been difficult to biochemically determine the H18:MHC-II binding. Here, we followed a different approach and generated MHC-II chimeras from the human leukocyte antigen DR (HLA-DR), which supports H18-mediated entry, and the nonclassical MHC-II molecule HLA-DM, which does not. In this context, viral entry was supported only by a chimera containing the HLA-DR α1, α2, and β1 domains. Subsequent modeling of the H18:HLA-DR interaction identified the α2 domain as central for this interaction. Further mutational analyses revealed highly conserved amino acids within loop 4 (N149) and β-sheet 6 (V190) of the α2 domain as critical for virus entry. This suggests that conserved residues in the α1, α2, and β1 domains of MHC-II mediate H18-binding and virus propagation. The conservation of MHC-II amino acids, which are critical for H18N11 binding, may explain the broad species specificity of this virus.